Sustainability of Supply Chain: Analysis of Post-COVID Economic Recovery Possibilities in Selected Sectors in the ASEAN Region - Alik Naha; Debasish Nandy (UIN Sunan Gunung Djati, 2022)
The environment of financial uncertainty among the Global Supply Chain networks has been fueled by the impact of Covid-19 which saw major economies around the world imposing months of lockdown, slowing the pace and flow of raw materials and manufactured products resulting in an economic slowdown. It has also brought to light the vulnerabilities and susceptibilities of emerging economies, like the ASEAN nations. This has resulted in collapsing of both domestic and foreign sectors like retail, accommodation, and food services. This has prompted the regional governments to boost up regional cooperation through structural reforms for sustainable economic recovery. In this respect, three sectors of tourism, agro-processing, and garments can be improvised, while two other sectors like electronics and E-trade have greater potential for future growth. In this context, the paper using content analysis and exploratory methods focuses on the impacts of Covid-19 on the sectors of tourism, agro-processing, and garments in the ASEAN region and the possible options for improvising the sectors of Electronics and E-trade to further economic recovery in the ASEAN region.